From Sex to Gender: A University Intervention to Reduce Sexism in Argentina, Spain, and El Salvador. (December 2014) - de Lemus, Soledad; Navarro, Laura; J. Velásquez, Marta; Ryan, Estrella; Megías, Jesús L.; Becker, Julia C.; Zawadzki, Matthew J.; Shields, Stephanie A.
<x xml:space="preserve">Abstract</x> We present an intervention to reduce gender prejudice in future professionals of social sciences in three samples from Argentina (N = 28), Spain (N = 83), and El Salvador (N = 67), with slight differences across countries. The program was based on scientific research on sexism and gender‐based power aimed at: (1) increasing awareness of gender inequalities; (2) reducing sexism in men and women; (3) providing participants with resources to implement social interventions. First the intervention is described, and then empirical evidence of its efficacy is provided. Results showed a reduction of benevolent sexism (BS), hostile sexism (HS), and essentialist views, and higher support for collective actions in Argentina (Study 1). HS and system‐justifying beliefs were reduced and support for collective action increased in Spain (Study 2). In El Salvador, HS, BS (marginally), system‐justifying, and homophobic beliefs were reduced (Study 3). Implications for interventions and policy making are discussed.